1978
DOI: 10.1037/0022-006x.46.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Use of paradoxical intention in a behavioral program for sleep onset insomnia.

Abstract: Sleep onset insomnia seems often to be based on performance anxiety associated with a client's fears of being able to fall asleep; in some cases, a therapeutic program might actually exacerbate this performance anxiety by focusing on the client's efforts to voluntarily control the sleep onset process. Five cases of sleep onset difficulty, unusually resistant to a conventional behavioral program for this problem (i.e., deep muscle relaxation and systematic desensitization), were exposed to paradoxical intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 4 publications
1
54
0
Order By: Relevance
“…The first wave of psychotherapy for insomnia included singlecomponent treatments that took a strictly behavioral focus. These treatments, which ranged from paradoxical intention [30][31][32] to stimulus control [33] to sleep restriction [34] among others, were administered as stand-alone interventions in clinical trials and were the first to gather empirical support as non-pharmacological treatments for insomnia. As the field of psychotherapy moved towards a focus on patterns of thinking during the second wave, insomnia treatments followed, with cognitive therapy for insomnia [35] emerging as a treatment specifically targeting the maladaptive beliefs about sleep and cognitive arousal commonly associated with the disorder.…”
Section: Third-wave Therapies In the Treatment Of Insomniamentioning
confidence: 99%
“…The first wave of psychotherapy for insomnia included singlecomponent treatments that took a strictly behavioral focus. These treatments, which ranged from paradoxical intention [30][31][32] to stimulus control [33] to sleep restriction [34] among others, were administered as stand-alone interventions in clinical trials and were the first to gather empirical support as non-pharmacological treatments for insomnia. As the field of psychotherapy moved towards a focus on patterns of thinking during the second wave, insomnia treatments followed, with cognitive therapy for insomnia [35] emerging as a treatment specifically targeting the maladaptive beliefs about sleep and cognitive arousal commonly associated with the disorder.…”
Section: Third-wave Therapies In the Treatment Of Insomniamentioning
confidence: 99%
“…The first study to empirically evaluate paradoxical intentions as an effective therapy for sleep-onset insomnia was a multiple case study conducted by Ascher and Efran (1978). Five clients complaining of severe insomnia that had proved refractory to a l0 week behavioral program of systematic desensitization and covert conditioning were given a paradoxical directive to remain awake as long as possible instead of trying to fall asleep.…”
Section: Insomniamentioning
confidence: 99%
“…They were told that by attempting to remain awake as long as possible they would circumvent the performance anxiety usually generated by their repetitive, unsuccessful attempts to fall asleep. Type B rationale employed a "reframing procedure" that has been effective in controlled, single and multiple case studies (Ascher & Efran, 1978;Re-linger & Bornstein, 1979;Relinger, Bornstein, & Mungas, 1978). These sutrjects were told that a common cause of insomnia is the anxiety-provoking thoughts people experience while waiting to fall asleep.…”
Section: Insomniamentioning
confidence: 99%
“…Turner and Ascher (1979) and Ascher and Turner (1979) found that a PI treatment program for sleep onset insomnia was significantly more effective than a placebo or waiting list control; no differences, however, were found among para doxical intention, progressive relaxation, and stimulus con trol (Turner and Ascher, 1979). Clients who failed to re spond to conventional behavioral treatment methods (relaxa tion and systematic desensitization) were helped by a para doxical instruction to try to remain awake as long as possi ble (Ascher and Efran, 1978 The manner in which PI instructions are administered also can be varied. Frankl (1960Frankl ( , 1975, for example, has described the use of humor in delivering his paradoxical directives.…”
Section: Paradoxical Intentionmentioning
confidence: 99%
“…Ascher and Turner (1979), Ascher and Efran (1978) high freedom; and low resistance, low freedom. Members of these groups were randomly assigned to treatments (paradoxi cal, self-control, and no treatment).…”
Section: Purpose Of Present Studymentioning
confidence: 99%